HAKEKAT TEORI PENGETAHUAN DAN KEBENARAN DALAM KONTEKS PENDIDIKAN ISLAM - Siti Rahmah; Khojir Khojir (Cross-border, 2021)
Discussing the theory of knowledge by itself talks about epistemology which discusses how knowledge occurs, the sources of knowledge, the origin of knowledge, methods of obtaining knowledge and the truth of knowledge. Humans always try to find the truth in their lives so that they can be accepted in the environment where they carry out social activities. The way to obtain knowledge for each individual is different, both through revelation (text), the five senses, the mind and the heart. Differences in the means of obtaining knowledge result in the Truth that is produced from the experience of each individual with other individuals will produce different levels of truth.